Rabbit model of rotavirus infection. - Conner, M E (1988)
A new small animal model was developed to study parameters of rotavirus infections, including the active immune response. Seronegative New Zealand White rabbits (neonatal to 4 months old) were inoculated orally with cultivatable rabbit rotavirus strains Ala, C11, and R2 and with the heterologous simian strain SA11. The course of infection was evaluated by clinical findings, virus isolation (plaque assay and enzyme-linked immunosorbent assay), and serologic response. All four strains of virus were capable of infecting rabbits as determined by isolation of infectious virus from intestinal contents or fecal samples, by seroconversion, or by a combination of these methods. The responses differed depending on the virus strain used for inoculation. Rabbits remained susceptible to primary infection to at least 16 weeks of age (upper limit examined). Virus excretion in intestinal contents was detected from 6 h to 7 days postinoculation. RNA electropherotypes of inocula and viruses isolated from rabbits were the same in all samples tested. Transmission of Ala virus and R2 virus but not SA11 virus from inoculated animals to uninoculated controls also occurred. In a challenge experiment with Ala virus, 74- and 90-day-old rabbits were rechallenged with Ala 5 weeks after a primary infection with Ala. Virus was excreted in feces from 2 to 8 days after the primary infection but was not excreted after challenge. These results indicate that the rabbit provides an ideal model to investigate both the primary and secondary active immune responses to rotavirus infections and to evaluate candidate vaccines.